Technology and application of staged fracturing weakening and relieving danger in hard roof - Yongquan SHAN; Dengyan GAO; Jianhua CHEN (Meikuang Anquan)
Aiming at the difficult problem of controlling dynamic pressure disaster induced by hard roof in Buertai Coal Mine in Shendong Mining Area, the expansion equation of pressure fractures in hard rock stratum is established, and the mechanism of advanced weakening of segmented hydraulic fracturing in hard roof under strong ground pressure is revealed. The formation law of segmented hydraulic fracturing in hard roof is analyzed by using three-dimensional fracture model numerical simulation, and the arrangement of roof fracturing drilling holes in 42108 working face of Buertai Coal Mine is determined, and the engineering application is carried out in the typical working face of Buertai Coal Mine in Shendong Mining Area. The application results show that the influence range of fracturing weakening is 150-450 m away from the cutting hole along the working face, 50-280 m upward along the working face. There are 11 zonal anomalies in the spatial distribution of fracturing fractures, and the direction of fracturing fractures is mostly 36°-54°, which is nearly parallel to the direction of maximum principal stress (NE55°- NE 77°). The extension radius of fracturing fracture increases, the vertical fracture height does not change obviously, and the width of fracturing fracture decreases slightly. The larger the interval between fracturing sections is, the smaller the influence radius of fracturing cracks is, fracture radius increases from 27 m to 35 m with the maximum decrease of 2.85 m, and the fracture development radius along the drilling direction is reduced from 15.2 m to 12.8 m. After entering the fracturing stage, the maximum value and average value of the cyclic pressure decreased by about 15.3% and 9.6% respectively, the average step length of the cyclic pressure decreased by about 8.1%. The engineering practice shows that the advanced hydraulic fracturing of hard roof effectively weakens the apparent strength of ground pressure and realizes the weakening of the dynamic disaster of hard roof.